Fosfomycin Pharmacokinetic Profile in Plasma and Urine and Quantitative Estimation in Prostate and Seminal Vesicles after One and Two Consecutive Doses of Oral Fosfomycin Trometamol in Healthy Male Volunteers - Andrea F. D. Di Stefano; Milko M. Radicioni; Francesca Morano; Alessandra Gentili; Elena Mallat; Dario Cuomo; Tonia Mazzarella; Veronica Di Fonzo (MDPI AG, 2022)
The present Phase I study investigated, for the first time, fosfomycin pharmacokinetics in humans after two 3 g doses of fosfomycin trometamol administered 27 h apart, according to the dose regimen recommended for the prophylactic indication for transrectal prostate biopsy in adult men. Plasma, urine and seminal plasma concentrations were measured after one and two consecutive doses in 24 healthy men, representative of the target population of the prophylactic indication. Prostate and seminal vesicle concentrations were estimated based on seminal plasma concentrations using a one-step regression method. The exposure to fosfomycin was very similar in rate (Cmax, tmax) after one and two doses. The AUC showed a minimal increment. On average, the apparent volume of distribution was high (>100 L), and the mean clearance had an intermediate value. The total amount and dose fraction of fosfomycin excreted in urine showed a small increment after two doses. The renal clearance was about 5 L/h. The fosfomycin concentration in the prostate and seminal vesicles showed that the antibiotic increased on average after two consecutive doses. This result confirmed the ability of fosfomycin to distribute into the prostate and into seminal vesicles after one single dose and that a two consecutive dose regimen increases the antibiotic availability inside these peripheral tissues.